2020
DOI: 10.1002/ijc.32993
|View full text |Cite
|
Sign up to set email alerts
|

Molecular description of ANGPT2 associated colorectal carcinoma

Abstract: Angiopoietin‐2 (ANGPT2) is a prognostic factor in metastatic colorectal cancer (CRC). Nevertheless, it remains to be elucidated which molecular characteristics make up the ANGPT2‐related poor‐prognosis CRC subset. Public transcriptomic datasets were collected from Gene Expression Omnibus GEO and with the TCGAbiolinks R‐package for the TCGA. After appropriate normalization, differential expression analysis was performed using Benjamini and Hochberg method for false discovery rate. Plasma from two prospective cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…In contrast, the M2 macrophage stimulated tumor cell migration through the enhanced secretion of a series of proteins that included matrix metalloproteinase 7 (MMP7) and angiopoietin 2 (ANGPT2). These results align with previous reports in the literature regarding the roles of CXCL9, CXCL10 and ANGPT2 [9][10][11][12] and also provide new potential targets (e.g. CXCL11 and MMP7) to limit tumor progression [13,14].…”
Section: Introductionsupporting
confidence: 92%
“…In contrast, the M2 macrophage stimulated tumor cell migration through the enhanced secretion of a series of proteins that included matrix metalloproteinase 7 (MMP7) and angiopoietin 2 (ANGPT2). These results align with previous reports in the literature regarding the roles of CXCL9, CXCL10 and ANGPT2 [9][10][11][12] and also provide new potential targets (e.g. CXCL11 and MMP7) to limit tumor progression [13,14].…”
Section: Introductionsupporting
confidence: 92%
“…Among the 35 eligible studies were 27 full-text articles ( 6 , 11 , 12 , 15 , 55–77 ) and 8 conference abstracts ( 78–85 ). Prognostic data were extracted from 21 studies, of which 2 were conference abstracts ( 6 , 11 , 15 , 57 , 58 , 60 , 61 , 63 , 64 , 66–73 , 75 , 77 , 80 , 81 ). The predictive value of the CMSs was assessed in 16 studies and 6 conference abstracts ( 12 , 15 , 55–57 , 59 , 62 , 64–67 , 69 , 72–74 , 76 , 78 , 79 , 82–85 ).…”
Section: Resultsmentioning
confidence: 99%
“…The meta-analyses into the prognostic value of the CMSs in local disease included patients from 11 cohorts. We found worse OS for CMS4 compared with CMS1 (stage I-III: HR = 3.28, 95% CI = 1.27 to 8.47; number of included cohorts [n] = 4) ( 15 , 61 , 66 , 70 ) and for CMS4 compared with CMS2 (stage I-III: HR = 2.60, 95% CI = 1.93 to 3.50; n = 3) ( 11 , 70 ). The same pattern was observed for the RFS and SAR ( Figure 2, A and B ) ( 11 , 58 , 70–72 , 75 ).…”
Section: Resultsmentioning
confidence: 99%
“…Some studies had shown that the relative expression level of the STC1 gene in cancer tissues was higher than that in adjacent normal mucosa; the high expression of STC1 was associated with a low postoperative survival rate. STC1 and other genes constitute a molecular network, which endows CRC with chemoresistance ( Tamura et al, 2011 ; Jary et al, 2020 ).VIP can regulate the growth and function of various immune cells and tumor cells. Compared with normal blood cells and other mesenchymal cells, various tumor cells, including colonic adenocarcinoma, pancreatic cancer, and carcinoid, express a large number of VIP receptors ( Virgolini et al, 1994 ).…”
Section: Discussionmentioning
confidence: 99%